The Scandinavian Trade Center: Chicago, Illinois - Daryl S. Rantis (Oz, 1984)
The site for the Scandinavian Trade Center is on Chicago's Magnificent Mile, just to the south of the Chicago River. Surrounding the trapezoidal site are many of the city's landmark buildings, including the Stone Container Building to the north and the Carbon and Carbide building further to the south...